THU0245 Early inflammatory arthritis clinics. do we need new diagnostic criteria?. (1st June 2001) - Salvador, G; Sanmartí, R; Cañete, JD; Gómez, A; Rodriguez, JR; Cerdá, D; Muñoz-Gómez, J
Abstract : Background: The usefulness of the diagnostic criteria for RA (ARA 1987) and spondyloarthropathy (European Group for Spondyloarthropaties 1993) in early inflammatory arthritis remains controversial. Objectives: To analyse the prevalence of inflammatory arthritis according to different diagnostic cathegories, in an early arthritis clinic. Methods: We recruited during one year period (Jan/00-Jan/01) 62 patients (38F, 24M) mean age 48 ys (range 17–79 ys), and mean disease duration of 3, 1 m (range 2 wks- 12 m). All patients had objective sinovitis in one or more joints with a disease duration between 2 weeks and one year. Septic arthritis and crystal deposition disease have been excluded. Poliarthritis was seen in 37 patients, oligoarthritis in 18 and monoarthritis in 7. At the time of inclusion 20 out of 62 patients fulfilled ARA (1987) criteria for RA (mean disease duration 4 m), 4 patients fulfilled European Group for Spondyloarthopathies criteria (mean disease duration 2 m), 2 patients had psoriatic arthritis (mean disease duration 5 m), 9 had self-limited arthritis (mean disease duration 3 weeks), in 4 of them an acute infection by PVB19 have been found. In 25 patients arthritis was considered unclassified (mean time disease duration 3 m). After a mean time follow-up of 6 months (3w-1 yr) 14 out of 20 patients of RA group still fulfilled RA criteria (70%), the other six fulfilled criteria for different diseases (2 Sjögren sindrome, 1 RS3PE, 1 Polymyalgia, 1 self-limited arthritis and 1 mixed connective tissue disease. Among unclassified arthritis group, 5/25 fulfilled RA criteria and 6/25 patients had oligoarthritis with HLA-B27+ which could suggest a probably spondyloarthropathy despite they didn?t fulfil European Group criteria. Other 3/25 patients developed: 1 Sjögren syndrome, 1 self-limited arthritis and 1 olygoarthritis ANA+ with Hashimoto?s thyroyditis. Results: Conclusion: Present diagnostic criteria for RA, have limited sensitivity and specificity to correctly classify early inflammatory arthritis. Some patients with unclassified arthritis probably have a spondyloarthropathy although they don?t fulfilled the European Group criteria. The development of new diagnostic criteria in patients with early arthritis is necessary.